2001
DOI: 10.1007/s002040100219
|View full text |Cite
|
Sign up to set email alerts
|

In vivo changes in antioxidant systems and protective role of melatonin and a combination of vitamin C and vitamin E on oxidative damage in erythrocytes induced by chlorpyrifos-ethyl in rats

Abstract: Reactive oxygen species (ROS) may be involved in the toxicity of chlorpyrifos-ethyl (CE) [O,O-diethyl-O-(3,5,6-trichloro-2-pyridyl)phosphorothioate]. We have, therefore, examined the in vivo effects of CE on the rat erythrocyte antioxidant system and evaluated the ameliorating effects of melatonin and a combination of vitamin E and vitamin C on the oxidative damage induced by CE. The experimental groups were: (1) control group, (2) CE-treated group (CE), (3) vitamin E plus vitamin C treatment group (Vit), (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
156
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(182 citation statements)
references
References 0 publications
24
156
0
2
Order By: Relevance
“…In the present study, malathion caused a significant decrease in activities of SOD, GSH and GPx in rat liver confirming the increased production of free radicals caused by administration of malathion. These findings are in accordance with those of Gultekin et al (2001) who reported that SOD activities decreased with increasing malathion concentration and incubation period. Also Rezg et al (2008) reported that sub chronic treatment with malathion, gradually decreased the activities of SOD in rat liver.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, malathion caused a significant decrease in activities of SOD, GSH and GPx in rat liver confirming the increased production of free radicals caused by administration of malathion. These findings are in accordance with those of Gultekin et al (2001) who reported that SOD activities decreased with increasing malathion concentration and incubation period. Also Rezg et al (2008) reported that sub chronic treatment with malathion, gradually decreased the activities of SOD in rat liver.…”
Section: Discussionsupporting
confidence: 93%
“…This protection may be attributed to phosphorylation and activation of endothelial nitric oxide syntheses in endothelial cells through modulation of protein kinase C. A signaling pathways by green tea resulting in endothelial dependant vasorelaxtion (Lorenz et al, 2004). So in our present study demonstrate that, the activity of the MDA in malathion exposed group increased 2 fold compared with that of the control one, these finding is in accordance with Gultekin et al (2001) who reported that MDA values increased with increasing organophosphorous compounds concentration and incubation period (Ranjbar et al, 2005), may be due to Lipid peroxidation was seen in erythrocytes and liver of rats when exposed to malathion orally for 4 weeks at dose of 5,25 and 75 mg/Kg, respectively (Abdollahi et al, 2004) While in groups treated by malathion plus vitamine c or malathion plus green tea there were a significant decrease in MDA values in comparison with malathion group may be due to The protective effect of vitamin c over malathion toxicity is likely to be mediated via the inhibition of free radical generation and enhancement of free radical scavenging activity (Suna et al, 2010) and Green tea prevents the loss of lipophilic antioxidant α-tocopherol by repairing tocopheryl radicals and protection of the hydrophilic antioxidant ascorbate (Skryzdlewska et al, 2002). Therefore, it may decrease the concentration of lipid free radicals and terminate initiation and propagation of lipid peroxidation (Guo et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies have shown that Mel is significantly better than the classic antioxidants in resisting free radical-induced molecular destruction (Gultekin et al, 2001;Baydas et al, 2002). Beneficial antioxidant effects of Mel have been recently shown in clinical settings for several chronic diseases, including patients with rheumatoid arthritis (Forrest et al, 2007), elderly patients with primary essential hypertension (KedzioraKornatowska, 2008), and females with infertility.…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of catalase in turn also prevents the SOD action. The decline in these antioxidant enzymes is mainly due to more ROS and lipid peroxidation [22]. The pretreatment with daidzein significantly increases the level SOD and catalase after CPA treatment.…”
Section: Discussionmentioning
confidence: 97%